Analysis of fruit wine advertising through neuromarketing tools - Venegas Cedeño, Josselyn Nicole; Villavicencio Tenezaca, Emerson David; Telenchano Toalombo, Gladys Yolanda; Zabala Jarrín, Harold Alexi (mktDESCUBRE, 2024)
This study investigates the impact of wine industry advertising on consumers' psychological attachment. Using Neuromarketing techniques, specifically eye tracking and GSR (galvanic bracelet), we analyze how certain visual and cognitive stimuli influence the public's perception and preference towards wine advertisements. The results reveal specific patterns of visual attention that suggest effective strategies to capture attention and generate greater emotional engagement in the audience, thus offering valuable insights for the formulation of more effective advertising strategies in this industry. Exploring these findings can provide insights to improve product positioning and build stronger, longer-lasting relationships with customers.